Total correction for tetralogy of Fallot in adolescents and adults - Aytaç, Aydın; Saylam, Argun; Yurdakul, Yurdakul; İkizler, Coşkun and Olga, Rüstem (The Turkish Journal of Pediatrics, 1980)
Total correction for tetralogy of Fallot in adolescents and adults is an uncommon practice, since this malformation is almost always corrected during early childhood period. Total correction performed in the late age group bears some disadvantages like fibrotic and calcific changes in some adult hearts and the ill effects of the long standing presence of palliative shunts in some cases. Although the old age carries some risk compared to early childhood, the mortality rate in this age group is within acceptable limits (8-15 %). It is concluded that the advanced age should not be a contrindication for total correction of tetralogy of Fallot.